2020
DOI: 10.1111/1756-185x.13823
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of safety, efficacy and cost between oral pulse cyclophosphamide versus intravenous cyclophosphamide pulse therapy in severe systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease.1 The spectrum of presentation varies from minor skin manifestation to life-threatening disease.2 Among the manifestations, renal and central nervous system involvement are major causes of morbidity and mortality. Renal involvement is a major complication, occurring in approximately 50% of patients.2 Patients with nephritis are at higher risk for progressive renal insufficiency.3 There is over 3 decades of clinical experience with cyclophos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…As the search was performed in 2019 relevant recent publications could have been missed. For example, Padiyar et al [ 54 ] has recently reported a comparison of the costs of oral CYC compared with intravenous CYC and Bell et al [ 55 ] recently published an abstract reporting the burden of illness in LN; it was reported that patients with LN have significantly higher ambulatory visits, ED visits, hospitalizations, and costs than patients without SLE. Miyazaki et al [ 56 ] also recently reported HCRU of patients with LN compared with patients without central nervous system (CNS) lupus or LN; a higher proportion of patients with LN had ≥ 1 hospitalization compared with patients without CNS lupus or LN.…”
Section: Discussionmentioning
confidence: 99%
“…As the search was performed in 2019 relevant recent publications could have been missed. For example, Padiyar et al [ 54 ] has recently reported a comparison of the costs of oral CYC compared with intravenous CYC and Bell et al [ 55 ] recently published an abstract reporting the burden of illness in LN; it was reported that patients with LN have significantly higher ambulatory visits, ED visits, hospitalizations, and costs than patients without SLE. Miyazaki et al [ 56 ] also recently reported HCRU of patients with LN compared with patients without central nervous system (CNS) lupus or LN; a higher proportion of patients with LN had ≥ 1 hospitalization compared with patients without CNS lupus or LN.…”
Section: Discussionmentioning
confidence: 99%
“…This may have obscured the efficacy of CYC, but it revealed side effects because some patients developed infections after receiving a low dose of CYC. Daily oral and pulse intravenous CYC administration have similar efficacies [ 25 , 26 ], which attenuated the heterogeneity of our control group. The short follow-up period, small sample size and the lack of a comparison with RTX at usual dose were also limitations.…”
Section: Discussionmentioning
confidence: 99%